Asymptotic representations of one class of solutions of a second-order difference equation with power nonlinearity - Khar’kov, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We obtain asymptotic representations for one class of solutions of a second-order difference equation with power nonlinearity.